2019
DOI: 10.1016/j.urology.2019.08.016
|View full text |Cite
|
Sign up to set email alerts
|

A Renal Cell Carcinoma with Biallelic Somatic TSC2 Mutation: Clinical Study and Literature Review

Abstract: OBJECTIVETo elucidate the effect of the biallelic somatic TSC2 mutations, identified in one adolescent patient, in renal cell carcinoma (RCC). METHODSMutation analyses, immunohistochemistry and real-time polymerase chain reaction (PCR) were conducted. RESULTSTwo novel somatic mutations of TSC2 in unilateral and solitary RCC samples from a 14-year-old female were identified. The pathological features suggest the tumor as a clear-cell renal cell carcinoma. In addition, immunohistochemistry revealed elevated leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Pten/Tsc1 deletion tumors may reflect the potent tumor suppressor functions of PTEN. Evidence has not yet linked the loss of a TSC gene and a second non-TSC gene in patient SEGAs (Henske et al, 1997;Chan et al, 2004;Bongaarts et al, 2017). Moreover, this same group did not find evidence that PTEN is mutated in SEGAs (Zordan et al, 2018).…”
Section: Modeling Tsc Segasmentioning
confidence: 95%
See 2 more Smart Citations
“…Pten/Tsc1 deletion tumors may reflect the potent tumor suppressor functions of PTEN. Evidence has not yet linked the loss of a TSC gene and a second non-TSC gene in patient SEGAs (Henske et al, 1997;Chan et al, 2004;Bongaarts et al, 2017). Moreover, this same group did not find evidence that PTEN is mutated in SEGAs (Zordan et al, 2018).…”
Section: Modeling Tsc Segasmentioning
confidence: 95%
“…And Tsc2 loss of heterozygosity (LOH), the genetic manifestation of the two-hit hypothesis, was detected in Eker renal tumors induced by mutagens and in Tsc2 heterozygous mice (Kubo et al, 1994;Kobayashi et al, 1997;Hino et al, 2002;Ma et al, 2005). Subsequent studies confirmed that LOH, also referred to as biallelic inactivation, occurs in TSC patient tumors and malformations including SEGAs and cortical tubers (Chan et al, 2004;Crino et al, 2010;Qin et al, 2010a;Bongaarts et al, 2017;Martin et al, 2017).…”
Section: The Molecular Genetics Of Tscmentioning
confidence: 98%
See 1 more Smart Citation
“…Actually, TSC2 encodes a tumor suppressor, which is capable of stimulating specific GTPases ( 32 , 33 ) and negatively regulate mTOR signaling ( 34 ). Somatic TSC2 mutation contributes to tumorigenesis, including renal cancer ( 35 ). Therefore, we speculated that these two mutations may inactivate both alleles of TCS2 , which unfortunately cannot be experimentally validated due to the long distance of these two mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation of the TSC genes in CCRCC is unusual but has been documented. Pang et al [ 43 ] reported a rare case of CCRCC with novel biallelic somatic mutations in TSC2 . This was a case of a 14-year-old female with VHL syndrome, where histologic findings were typical of CCRCC morphology.…”
Section: Discussionmentioning
confidence: 99%